Complementarity of electrophoretic, mass spectrometric, and gene sequencing techniques for the diagnosis and characterization of congenital disorders of glycosylation. Issue 24 (3rd July 2018) - Bruneel, Arnaud; Cholet, Sophie; Drouin‐Garraud, Valérie; Jacquemont, Marie‐Line; Cano, Aline; Mégarbané, André; Ruel, Coralie; Cheillan, David; Dupré, Thierry; Vuillaumier‐Barrot, Sandrine; Seta, Nathalie; Fenaille, François
Abstract: Congenital disorders of glycosylation (CDG) are rare autosomal genetic diseases affecting the glycosylation of proteins and lipids. Since CDG‐related clinical symptoms are classically extremely variable and nonspecific, a combination of electrophoretic, mass spectrometric, and gene sequencing techniques is often mandatory for obtaining a definitive CDG diagnosis, as well as identifying causative gene mutations and deciphering the underlying biochemical mechanisms. Here, we illustrate the potential of integrating data from capillary electrophoresis of transferrin, two‐dimensional electrophoresis of N‐ and O‐ glycoproteins, mass spectrometry analyses of total serum N‐ linked glycans and mucin core1 O‐ glycosylated apolipoprotein C‐III for the determination of various culprit CDG gene mutations. "Step‐by‐step" diagnosis pathways of four particular and new CDG cases, including MGAT2‐CDG, ATP6V0A2‐CDG, SLC35A2‐CDG, and SLC35A3‐CDG, are described as illustrative examples.